Modelling temperature and concentration dependent solid/liquid interfacial energies. Issue 1 (2nd January 2016) - Lippmann, Stephanie; Jung, In-Ho; Paliwal, Manas; Rettenmayr, Markus
ABSTRACT: Models for the prediction of the solid/liquid interfacial energy in pure substances and binary alloys, respectively, are reviewed and extended regarding the temperature and concentration dependence of the required thermodynamic entities. A CALPHAD-type thermodynamic database is used to introduce temperature and concentration dependent melting enthalpies and entropies for multicomponent alloys in the temperature range between liquidus and solidus. Several suitable models are extended and employed to calculate the temperature and concentration dependent interfacial energy for Al–FCC with their respective liquids and compared with experimental data.